Commercial resources of saffron cod Eleginus gracilis in the Russian waters of the Far-Eastern Seas - O. V. Novikova; M. V. Rakitina; A. V. Metlenkov; L. A. Chernoivanova; A. Yu. Nemchenko (Известия ТИНРО, 2023)
Saffron cod Eleginus gracilis, being a typical representative of the elittoral ichthyocene, is an important commercial species in the coastal areas of the Far-Eastern Seas. Small- and medium-sized vessels equipped with both active fishing gears as Danish seine or trawl and fixed nets are used for fishery of this species, it is also popular for amateur and sport fishing from the sea ice. The portion of saffron cod in the total landing is the largest in the Karaginsky fishing subzone (8.1 %) and West-Kamchatka fishing subzone (3.6 %). Annual catch of the species in the Far-Eastern Seas fluctuated in 2003–2022 from 16.7 . 103 to 50.6 . 103 t, on average 33.9 . 103 t. The bulk of this value was caught in the waters at Kamchatka, mostly at its western coast where the average catch was 10.5 . 103 t annually in the last decade. The main fishing grounds of saffron cod are located within the Kamchatka-Kuril, West-Kamchatka, East-Sakhalin and Karaginsky fishing subzones, whereas the stocks at Primorye and sparsely populated coasts of the western Okhotsk Sea and northwestern Bering Sea are underexploited. The saffron cod CPUE reaches 4.5 t per hour of trawling on the shelf of West Kamchatka. The biomass of saffron cod is estimated recently as 197.4 . 103 t in the West-Kamchatka subzone, 100.4 . 103 t in the Karaginsky subzone, 32.8 . 103 t in the West Bering Sea fishing zone, 17.2 . 103 t in the Petropavlovsk-Commander subzone, 17.1 . 103 t in the East-Sakhalin sunzone, and 8.7 . 103 t in the North Okhotsk Sea subzone. The species is distinguished by significant fluctuations of commercial stocks caused by both environmental impacts on its recruitment and fishing pressure. The strong year-classes appear usually in relatively warm or moderate environmental conditions. In modern times, abundance and biomass of almost all exploited stocks of saffron cod in the Far-Eastern Seas excess their average long-term level or fluctuate around, so the state of their populations is considered as quite satisfactory.